Peningkatan Pemahaman Siswa Terhadap Teks Eksposisi Melalui Strategi Membaca Pemahaman SQ3R pada Siswa Kelas VII Mts Wachid Hasyim Surabaya - Hernik Farisia; Raden Syafuddin; M. Na'im; Erdin Lies Tyanto (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2021)
Based on preliminary study, it was found that 62% of students at the seventh grade of MTs Wachid Hasyim Surabaya were not able to answer inferential and referential question to fulfil reading comprehension. Therefore, this study used classroom action research by implementing Survey, Question, Read, Recite, dan Review (SQ3R) reading strategy to improve students’ ability in reading comprehension. This research was conducted in two cycles. The result showed that 83% students were able to answer inferential and referential question to understand the text at the first cycle and 97 % at the second cycle. It means that there was an increase of 14% from the first cycle to the second cycle. Meanwhile, 79% students had reached mastery learning to rewrite the text on students’ own language.